Moldagem e comparação de propriedades de compósitos de poli(butileno adipato-co-tereftalato) reforçados com tecidos de fibras vegetais - Maciel, Cristiane Carla (2019)
In recent years, the increasing volume of polymer resin production and use has generated environmental problems caused by the post-consumption disposal of these materials, which become huge amounts of waste due to the difficulty of biodegradation and also the low use in recycling processes. Thus, the present work sought the development of polymeric composites with the use of a thermoplastic and biodegradable polymer matrix (PBAT). For the molding of the composites were used jute vegetable fibers, which are of renewable source, easy to obtain and low cost. In the case, three different commercial types of fiber fabric were used: jute (F9), jute and cotton (I33) and jute 2X2 with weights of 382 g / m2, 361 g / m2 and 438 g / m2 respectively. The moldings of the materials were made in metal mold coupled in a hydraulic press, using the hot compression method, followed by cooling at room temperature. After the moldings, the materials were cut for the analysis of spectroscopy in the infrared region by Fourier transform (FTIR), thermal properties by thermogravimetric analysis (TGA/DTG), dynamic-mechanical thermal analysis (DMTA), mechanical tests (tensile and impact), scanning electronic microscopy (SEM) analysis, crystallinity (XRD) and contact angle. FTIR analysis revealed only O-H bands present in the composite samples due to the presence of the fibers. Regarding the TGA/DTG analysis, it was observed that the insertion of the reinforcement in the matrix caused a decrease of 3 to 4% in the thermal stability of the composites in relation to the PBAT. From the results of the mechanical tests of traction and impact it was possible to observe improvements of up to 208% in the maximum tensile strength and 142% in the impact resistance. According to the SEM images, fibers / polymer matrix interaction was observed, revealing a certain interfacial adhesion. The percent crystalline phase of PBAT (17.79%) was obtained by the XRD diffractogram. In the contact angle analysis, the PBAT polymer and the composites presented hydrophobic characteristics on the respective surfaces. Therefore from the set of analyzes performed in this work it was possible to characterize and compare the three different types of jute fiber fabrics reinforced composites with the PBAT polymer. In addition, it was possible to verify that the composites presented superior mechanical properties compared to PBAT polymer without reinforcement.